P-104 SECURE: An Observational Study of Certolizumab Pegol in Crohn's Disease—Events of Interest Analysis with 5869 Patient-Years at Risk. (March 2016) - Lee, Scott; Wolf, Doug; Feagan, Brian; Lichtenstein, Gary; Andrews, Elizabeth; Stidham, Ryan; Aberra, Faten; Aguilar, Humberto; Kayhan, Cem; Kosutic, Gordana; Sen, David; Golembesky, Amanda; et al.
Abstract : Background: Tumor necrosis factor-alpha antagonists are associated with an increased risk of serious infections and some malignancies. The objective of the SECURE registry is to evaluate these safety outcomes in patients with Crohn's disease (CD) treated with certolizumab pegol (CZP) versus other CD treatments. Methods: SECURE is a long-term registry of patients with CD. Patients were enrolled in either the CZP cohort (those who had received CZP for ⩽12 months or were about to receive CZP at enrollment) or the comparison cohort (CO; those receiving corticosteroids, immunosuppressants, or non-CZP biologics). The cutoff date for this interim analysis was March 31, 2014. Exposure time for all events, excluding malignancies, took into account treatment switching. Observational time was divided into 4 mutually exclusive categories: CZP cohort (exposure to CZP only); CO cohort (exposure to other CD treatments); Overlap cohort (exposure overlap between CZP and other CD treatments); and Gap cohort (no exposure to any CD treatment). Incidence rates and 95% confidence intervals (CIs) per 100 patient-years were calculated for adverse events of interest. Serious adverse events (SAEs) were summarized as percentages of patients reporting ≥1 SAE per system organ class. Owing to the longer latency, the exposure times for malignancies were calculated differently and reported elsewhere. 1 Results: A total of 2453 (1097 CZP; 1356 CO) patients were enrolled; 1464 patients (59.7%) were ongoing and 989 patients (40.3%) had discontinued at cutoff. At enrollment, the mean age of patients was 40.6 years (range, 7.3–88.6); more patients had moderate to severe or severe disease in the CZP versus CO cohort (moderate to severe, 40.7% versus 20.1%; severe, 9.6% versus 2.7%) and the proportion of patients in remission was higher for CO versus CZP (37.6% versus 9.6%). Planned exposure for all patients based on cohort assignment at enrollment was 5868.8 patient-years (2477.7 and 3391.1 patient-years for CZP and CO, respectively). When accounting for treatment switching, actual exposure to CZP only was 601.1 patient-years; 3465.9 patient-years to CO only; 705.1 patient-years to concurrent CZP/CO exposure; and 1096.8 patient-years with a gap in exposure. The incidence rates of serious infections were: CZP only, 0.35 (95% CI, 0.04–1.25); CO only, 0.53 (95% CI, 0.32–0.84); Overlap, 1.33 (95% CI, 0.61–2.53); and Gap, 0.34 (95% CI, 0.07–0.99). The percentage of patients with SAEs was higher in the CZP cohort versus CO versus Overlap versus Gap for metabolism/nutrition disorders (1.2% versus 0.7% versus 0.9% versus 0.6%) and general disorders/administration site conditions (1.0% versus 0.5% versus 0.3% versus 0.8%), but lower for gastrointestinal disorders (7.0% versus 9.4% versus 14.0% versus 6.3%), infections (2.2% versus 4.3% versus 6.4% versus 2.2%), and surgical/medical procedures (1.3% versus 2.2% versus 1.3% versus 1.0%). Conclusions: These interim results showed that the incidence of infections during CZP treatment was similar to that with other CD treatments. Although the number of patient-years at risk in this analysis was relatively small, these data are consistent with the established CZP safety profile.